2017
DOI: 10.1177/0954407017701554
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the vehicle driving stability region based on the bifurcation of the driving torque and the steering angle

Abstract: Integrated control systems for vehicle-handling stability are usually based on the steering bifurcation mechanism. The best integrated control performance is obtained by coordinating different control methods. However, in vehicle steering and driving conditions, the coupling characteristics of the longitudinal forces and the lateral forces of the tyres must lead to changes in the bifurcation characteristics. The corresponding vehicle dynamics stability region has to be redetermined. The corresponding integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Based on the nonlinear 3DOF vehicle model and magic-formula tire model [26], by solving the equilibrium points under a certain speed, it is found that the lateral velocity and yaw rate are approximately proportional relation in the steady branch. The steady state is reference state in stability control, so the vehicle reference lateral velocity can be expressed by the equation:…”
Section: Reference Yaw Ratementioning
confidence: 99%
“…Based on the nonlinear 3DOF vehicle model and magic-formula tire model [26], by solving the equilibrium points under a certain speed, it is found that the lateral velocity and yaw rate are approximately proportional relation in the steady branch. The steady state is reference state in stability control, so the vehicle reference lateral velocity can be expressed by the equation:…”
Section: Reference Yaw Ratementioning
confidence: 99%
“…The approach has also been used in current literature directly related to the automotive industry, in areas such as vehicle dynamics, wheel and suspension dynamics, permanent synchronous motors and braking systems. A bifurcation analysis helped determine how driving speed and steering angle 12 and torque and steering angle 13 affect the stability in a cornering vehicle. In addition, the lateral dynamics of a vehicle driving straight ahead was also studied.…”
Section: Introductionmentioning
confidence: 99%
“…Stability maps with steering angle and the drive torque as bifurcation parameters have been presented in [6] before. In contrast to this study, equilibrium points of an understeer vehicle (without Hopf bifurcation) were considered for continuation, while supercritical Hopf bifurcations have been pointed out for different characteristics of oversteer vehicles in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Next to [6], longitudinal slip and respective longitudinal vehicle dynamics have been included in [12,13], resulting in smaller areas of attraction to a stable equilibrium point. As a further extension to bifurcation analysis of equilibrium points, a method to use bifurcation and continuation procedures also for evaluation of vehicle stability during acceleration and braking has been proposed in [14].…”
Section: Introductionmentioning
confidence: 99%